2013
DOI: 10.4490/algae.2013.28.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Cold-tolerant strain of Haematococcus pluvialis (Haematococcaceae, Chlorophyta) from Blomstrandhalvøya (Svalbard)

Abstract: A new cold-adapted Arctic strain of Haematococcus pluvialis from Blomstrandhalvøya Island (Svalbard) is described. This strain is predominantly always in non-motile palmelloid stage. Transmission electron microscopy showed the presence of very thick cell wall and abundant lipid vesicles in the palmelloids, including red and green cells. The external morphology of the non-motile palmelloid and motile bi-flagellated cells of our strain is similar to H. pluvialis; however it differs from H. pluvialis in physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 15 publications
(24 reference statements)
2
14
0
Order By: Relevance
“…When the old cultures were inoculated into fresh media, the newly produced flagellated cells transformed into non-motile palmelloid cells within only 1-2 days. These physiological characteristics were similar to the previous report of H. pluvialis, which were mostly in the palmelloid stage [25]. In this study, Haematococcus sp.…”
Section: Growth Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…When the old cultures were inoculated into fresh media, the newly produced flagellated cells transformed into non-motile palmelloid cells within only 1-2 days. These physiological characteristics were similar to the previous report of H. pluvialis, which were mostly in the palmelloid stage [25]. In this study, Haematococcus sp.…”
Section: Growth Characteristicssupporting
confidence: 92%
“…The genus Haematococcus described by Flotow (1844) is a freshwater unicellular microalga belonging to the class Chlorophyceae [10,36]. It is widely distributed worldwide, and its natural habitats are characterized by their unstable temporary conditions, such as small rock pools, water holes, and other small natural (or artificial) water bodies, including birdbaths [10,25]. To date, a total of seven species have been taxonomically classified in the genus Haematococcus at AlgaeBase (http://www.algaebase.org/), and H. pluvialis Flotow has been thoroughly investigated among these species.…”
Section: Introductionmentioning
confidence: 99%
“…Klochkova et al. () reported a cold tolerant strain of H. lacustris capable of growing at 4°C–10°C. Allewaert et al.…”
Section: Resultsmentioning
confidence: 99%
“…In a few studies slightly lower temperatures ranging between 14°C and 18°C have been employed (Harker et al 1995). Klochkova et al (2013) reported a cold tolerant strain of H. lacustris capable of growing at 4°C-10°C. Allewaert et al (2015) in their recent studies on European Haematococcus species observed high intraspecific variation in optimal temperature and maximum growth rate.…”
Section: Resultsmentioning
confidence: 99%
“…This microalga can be usually found in temperate regions around the world and has been isolated from Europe, Africa, North America, and Himachal Pradeslv India (Pringsheim, 1966 ; Suseela and Toppo, 2006 ). It has been also found across diverse environmental and climate conditions: in brackish water on the rocks on the seashore (Chekanov et al, 2014 ); freshwater basin in the rock filled with melted snow on Blomstrandhalvøya Island (Norway) (Klochkova et al, 2013 ); dried fountain near Rozhen, Blagoevgrad in Bulgaria Gacheva et al, 2015 , freshwater fishpond in Bihor, Romania (Dragos et al, 2010 ); rooftop surface of a building of KIOST in Seoul Korea (Kim et al, 2015 ). It is well suited for survival under conditions of expeditious and extreme in light, temperature, and salt concentration that would be deleterious to many other microalgae, due to its ability to encyst (become enclosed by thick membrane) in a rapid manner (Proctor, 1957 ).…”
Section: Biology Of H Pluvialismentioning
confidence: 99%